Buzhongyiqi Decoction Protects Against Loperamide-Induced Constipation by Regulating the Arachidonic Acid Pathway in Rats - Ju, Wan-Jun; Zhao, Ze-kuo; Chen, Shao-Li; Zhou, Dan-dan; Yang, Wen-Ning; Wen, Xiao-Ping; Du, Guang-Li (Frontiers in Pharmacology, 2020)
Constipation is a common gastrointestinal disorder without effective treatment approach. Buzhongyiqi decoction (BZYQD) is a classical formula that has been commonly used for gastrointestinal disorders for nearly one thousand years. In this study, we aimed to investigate the protective effect of BZYQD against loperamide-induced constipation and its potential underlying mechanism. Rats with loperamide-induced constipation were orally administered BZYQD. BZYQD treatment obviously increased the small intestinal transit rate and alleviated colon tissue pathological damage. Subsequently, serum metabolomics study was performed to identify the metabolites affected by BZYQD. Metabolomics identified that the levels of 17 serum metabolites, including prostaglandin E2 (PGE2) and arachidonic acid (AA), were significantly changed in the BZYQD-treated group compared with those in the loperamide-induced group. The main pathway that BZYQD affected was that of AA metabolism. BZYQD treatment could downregulate the cyclooxygenase-2 expression and decrease production of the proinflammatory mediator PGE2. The AA metabolic pathway is the main pathway for inflammatory mediator production. Further study revealed that BZYQD administration decreased serum levels of the inflammatory factors IL-1β and TNF-α. Moreover, BZYQD treatment inhibited phosphorylation of the nuclear transcription factor NF-κB, and down-regulated expression of the inflammatory factors IL-1β and IL-6 in the constipated rat colon.In conclusion, the present study suggested that BZYQD exerted a protective effect against loperamide-induced constipation, which may be associated with its role in regulation of multiple metabolic pathways.